KOMPETENSI PROFESIONAL DAN KOMPETENSI PEDAGOGIK GURU DALAM PENGELOLAAN PROSES PEMBELAJARAN DI DALAM KELAS (STUDI KASUS DI MI DARUL ULUM 2 DADI REJO) - Khasbi Ainun Najib; Anistalia Damayanti; Risky Putri Ayu Lestari (CV. ADIBA AISHA AMIRA, 2025)
This research aims to analyze the professional competence and pedagogical competence of teachers in managing the learning process in the classroom, with a case study at MI Darul Ulum 2 Dadi Rejo. Teachers' professional and pedagogical competence is a key factor in creating an effective and conducive learning environment for students. This research seeks to identify the extent to which teachers apply these two competencies in daily teaching practice and their impact on the quality of learning. The research method used is a qualitative descriptive approach, with data collection techniques through direct observation, interviews with teachers, and analysis of related documents. This research involved MI Darul Ulum 2 teacher Dadi Rejo as the main respondent to obtain a more comprehensive picture regarding the application of their professional and pedagogical competencies in the classroom. The research results show that teachers at MI Darul Ulum 2 Dadi Rejo have a good level of competence in professional aspects, especially in planning lessons and mastering teaching materials. However, challenges are still found in the pedagogical aspect, especially related to the differentiation of teaching methods and effective classroom management for students with diverse learning needs. These findings indicate the need for ongoing training and mentoring for teachers to further improve their pedagogical skills. The conclusion of this research confirms that increasing teacher professional and pedagogical competence is very important in optimizing the learning process in the classroom. The recommendations put forward include developing more specific training programs according to teacher needs as well as implementing more varied learning strategies in order to improve the overall quality of education.